GUGATAN PERKARA KEWARISAN YANG TIDAK DAPAT DITERIMA (NIETONTVANKELIJKE VERKLAARD) OLEH HAKIM DI PENGADILAN AGAMA KELAS IA PADANG - Roza Afriadi, Mardius , (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Inheritance cases that cannot be resolved amicably can be filed in court. Islamic inheritance cases are cases that have not been widely used by the public, so many Islamic inheritance cases that are filed cannot be accepted by judges. In the Padang religious court, for example, there was an inheritance lawsuit that was declared unacceptable or NO (niet ontvankelijke verklard). As for the reason for not accepting the lawsuit because the lawsuit is obscur libel, that is, it is not clear and certain, with a legal basis referring to Rv article 8 paragraph 3 and the parties to the lawsuit must be fully identified according to (Jurisprudence of the Supreme Court of the Republic of Indonesia dated 15-5 -1975 number 151 K/Sip/1975.) was declared inadmissible because in the lawsuit there were several formal requirements that were not met, while the conditions were that the address of the defendant was blurred or did not meet the clear and definite requirements because when the bailiff summoned the defendant to the address submitted by the plaintiff it turns out that the defendant does not live in Padang as proposed by the plaintiff, based on the narrative of the local village head the defendant lives and works in Jakarta, so this case is not the authority of the Padang religious court in deciding it.